ENVIRONMENTAL IMPACTS OF SHRIMP FARMING IN CHAKARIA UPAZILA OF COX’S BAZAR IN BANGLADESH - Md. Humayain Kabir (Zibeline International, 2021)
Aquaculture has become one of the fastest-growing economic sub-sectors of the Bangladesh economy, providing protein-rich food, the source of employment and foreign currency earnings. Therefore, shrimp farming is very much common in the brackish water which affects the coastal natural ecosystem and livelihood of the coastal communities, prticularly in Chakaria Upazila of Cox’s Bazar district. Due to rapid and unplanned growth of this farming, socio-ecological systesms has been changing. This study aims to assess shrimp farming’s environmental, social, and economic impacts in Chakaria upazila in Bangladesh. Soil sample was collected to determine the environmental impacts of shrimp farming. Besides, we selected the shrimp farmers, rice producers, and alternative shrimp-rice producers through simple random sampling. Purposive sampling was conducted to choose the other stakeholders. A semi-structured questionnaire was developed for interviewing different stakeholders. We found that, because of the high economic benefit, high production rate in short time, and availability of brackish water, the people in this Upazila are attracted to continue the shrimp farming. As a result, mangrove forest and agricultural land converted into shrimp farming. Our soil analysis showed that organic matter content in was low (0.25-3.56%). In addition to this, most people suffer from water-borne diseases during the flooding period. We also found clear evidene of shortage of safe drinking water due to salinity intrusion in grounwater. The tendency of raring livestock such as cow, goat, and buffalo decreased due to insufficient grazing land. The study also revealed that some internal conflicts exist between different stakeholders in Chakararia Upazila. Most local shrimp fry collectors collect fry from the tidal river and use an unscientific traditional method which was harmful for the other aquatic fish population. Poor quality of larvae supply from hatchery caused various diseases in cultivated ghers and ponds. The findings from this study provide useful information for sustainable coastal zone management in Bangladesh to build a more resilient coastal communities.